2015
DOI: 10.3389/fncel.2015.00172
|View full text |Cite
|
Sign up to set email alerts
|

Leptin is required for hypothalamic regulation of miRNAs targeting POMC 3′UTR

Abstract: The central nervous system (CNS) monitors modifications in metabolic parameters or hormone levels and elicits adaptive responses such as food intake regulation. Particularly, within the hypothalamus, leptin modulates the activity of pro-opiomelanocortin (POMC) neurons which are critical regulators of energy balance. Consistent with a pivotal role of the melanocortin system in the control of energy homeostasis, disruption of the POMC gene causes hyperphagia and obesity. MicroRNAs (miRNAs) are short noncoding RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Using in situ hybridization, we demonstrated that these three miRNAs are present in the POMC neurons of the ARC (Derghal et al, 2015). In addition, there is an increase of the expression of mir-383, mir-384-3p, and mir-488 in the hypothalamic structures of ob/ob and db/db mice models (Derghal et al, 2015) (Figure 2). The intraperitoneal and intracerebroventricular injection of leptin decreased the expression of these miRNAs in the hypothalamus of wild type and ob/ob mice suggesting a role of leptin in the expression of mir-383, mir-384-3p, and mir-488 (Derghal et al, 2015) (Figure 2).…”
Section: The Microrna and The Melanocortin Systemmentioning
confidence: 95%
See 3 more Smart Citations
“…Using in situ hybridization, we demonstrated that these three miRNAs are present in the POMC neurons of the ARC (Derghal et al, 2015). In addition, there is an increase of the expression of mir-383, mir-384-3p, and mir-488 in the hypothalamic structures of ob/ob and db/db mice models (Derghal et al, 2015) (Figure 2). The intraperitoneal and intracerebroventricular injection of leptin decreased the expression of these miRNAs in the hypothalamus of wild type and ob/ob mice suggesting a role of leptin in the expression of mir-383, mir-384-3p, and mir-488 (Derghal et al, 2015) (Figure 2).…”
Section: The Microrna and The Melanocortin Systemmentioning
confidence: 95%
“…In addition, there is an increase of the expression of mir-383, mir-384-3p, and mir-488 in the hypothalamic structures of ob/ob and db/db mice models (Derghal et al, 2015) (Figure 2). The intraperitoneal and intracerebroventricular injection of leptin decreased the expression of these miRNAs in the hypothalamus of wild type and ob/ob mice suggesting a role of leptin in the expression of mir-383, mir-384-3p, and mir-488 (Derghal et al, 2015) (Figure 2). Altogether, these observations strongly suggest that miRNAs are important for the central regulation of energy homeostasis by melanocortin pathway.…”
Section: The Microrna and The Melanocortin Systemmentioning
confidence: 96%
See 2 more Smart Citations
“…More recently, miRNAs that are specific for metabolic diseases have been identified, and their function and target pathways elucidated. Indeed, miRNAs have been demonstrated to be important regulators of a number of critical metabolic functions, such as insulin secretion in the pancreas [26], lipid and glucose metabolism in the liver [27], and leptin signaling in the hypothalamus [28]. Unlike the role of secreted proteins such as cytokines and proteins, the role of miRNAs in intercellular communication in these conditions remains undefined.…”
Section: Mirnas Involved In Cell-to-cell Communication In Metabolic Dmentioning
confidence: 99%